Characterization of the fungal genus Sphaerellopsis associated with rust fungi: species diversity, host-specificity, biogeography, and in-vitro mycoparasitic events of S. macroconidialis on the southern corn rust, Puccinia polysora - Paula Andrea Gómez-Zapata; Jorge Ronny Díaz-Valderrama; Samira Fatemi; Cristhian Orlando Ruiz-Castro; M. Catherine Aime (IMA Fungus)
Abstract Sphaerellopsis species are putative hyperparasites of rust fungi and may be promising biological control agents (BCA) of rust diseases. However, few detailed studies limit potential BCA development in Sphaerellopsis. Here, we explored the biogeography, host-specificity, and species diversity of Sphaerellopsis and examined the early infection stage of one species, S. macroconidialis, to infer its trophic status. We randomly screened 5,621 rust specimens spanning 99 genera at the Arthur Fungarium for the presence of Sphaerellopsis. We identified 199 rust specimens infected with Sphaerellopsis species on which we conducted morphological and multi-locus phylogenetic analyses. Five Sphaerellopsis species were recovered, infecting a total of 122 rust species in 18 genera from 34 countries. Sphaerellopsis melampsorinearum sp. nov. is described as a new species based on molecular phylogenetic data and morphological features of the sexual and asexual morphs. Sphaerellopsis paraphysata was the most commonly encountered species, found on 77 rust specimens, followed by Sphaerellopsis macroconidialis on 56 and S. melampsorinearum on 55 examined specimens. The type species, Sphaerellopsis filum, was found on 12 rust specimens and Sphaerellopsis hakeae on a single specimen. We also recovered and documented for the first time, the sexual morph of S. macroconidialis, from a specimen collected in Brazil. Our data indicate that Sphaerellopsis species are not host specific and furthermore that most species are cosmopolitan in distribution. However, S. paraphysata is more abundant in the tropics, and S. hakeae may be restricted to Australia. Finally, we confirm the mycoparasitic strategy of S. macroconidialis through in-vitro interaction tests with the urediniospores of Puccinia polysora. Shortly after germination, hyphae of S. macroconidialis began growing along the germ tubes of P. polysora and coiling around them. After 12 days of co-cultivation, turgor loss was evident in the germ tubes of P. polysora, and appressorium-like structures had formed on urediniospores. The interaction studies indicate that Sphaerellopsis species may be more effective as a BCA during the initial stages of rust establishment.